Efficacy and safety of radiotherapy/chemoradiotherapy combined with immune checkpoint inhibitors for locally advanced stages of esophageal cancer: A systematic review and meta-analysis - Wu, Jing; Deng, Rong; Ni, Tingting; Zhong, Qin; Tang, Fei; Li, Yan; Zhang, Yu (Frontiers in Oncology, 2022)
Background Radiotherapy (RT)/Chemoradiotherapy (CRT) are important treatments for all stages of esophageal cancer (EC). The combination of immune checkpoint inhibitors (ICIs) with RT/CRT seems to be promising avenue for the treatment of EC. Therefore, a systematic review and meta-analysis was performed in order to assess the safety and efficacy of RT/CRT and ICI combination therapy for EC patients. Methods PubMed and several other databases were searched (according to specific criteria) to find relevant studies published prior to the 31st of December 2021. Results 1962 articles were identified for screening, and six trials containing 668 patients were identified and pooled to determine the one- and two-year overall survival (OS), which were 84.5% (95% confidence interval (CI): 69.9%-100%) and 68.3% (95% CI: 49.0%-95.1%), respectively. Additionally, the rate of pooled grade 3-5 adverse reactions was 41.0% (95% CI: 31.2%-51.2%). The rate of specific grade 3-5 adverse reactions are as follows: lymphopenia (36.8%-60%), esophagitis (20%), anastomotic leakage (18%), esophageal fistula (10%), pain (10%), leukopenia (5.3%-10%), esophageal hemorrhage (2.5%-5%), chyle leakage (3%), fatigue (5%), cough (2.7%-5%), diarrhea (2.7%), pulmonary embolism (2.5%) and allergic reaction (2.5%). The pooled rate of pneumonitis of grade 3-5 and grade 1-5 was 0.8% (95% CI: 0.1%-0.16%, I2: 0%) and 5.4% (95% CI: 2.0%-14.2%, I2: 82%). For thoracic complication, esophagitis was 63.6% (95% CI: 42.4%-80.6%), which appeared to be more frequent with the combination of ICIs to RT/CRT (12%-37.7%). Other thoracic complications include esophageal hemorrhage (2.5%-10%), esophageal fistula (6%-10%) and anastomotic leakage (6%-21%). Additionally, some of the trials did not report cardiac related adverse reactions. The subgroup analyses also revealed that the pooled rate patients with grade 3-5 pneumonitis was higher for CRT/RT with concurrent and sequential ICI treatment (1.9%) than other groups (0.8%). Conclusion This study suggests that the addition of ICIs to RT/CRT for EC patients may be both safe and feasible. However, larger randomized studies are needed to confirm these results.